A bifunctional electrochemical flow cell integrating ammonia production and electricity generation for renewable energy conversion and storage. (9th November 2022) - Pan, Zhefei; Liu, Yun; Zhang, Zhewei; Zhao, Zhen; Zhu, Jie; Chen, Rong; An, Liang
Abstract: Renewable energy has rapidly advanced in the global energy system, triggering the visible development of energy storage technologies in recent decades. Among them, the electricity-fuel-electricity approach is an effective way for the storage and utilization of renewable power. In this work, a bifunctional electrochemical flow cell integrating both ammonia production and electricity generation modes is developed for renewable energy conversion and storage. Ammonia, a hydrogen carrier having a high hydrogen content of 17.6 wt %, is relatively easier to convert to liquid phase for large-scale storage. The long-distance ammonia transport can reliably depend on the established infrastructure. In addition, as a carbon-free fuel beneficial for achieving the goal of carbon-neutrality, ammonia is considered as an environmentally benign and cost-effective mediator fuel. This flow cell is able to operate via two modes, i.e., an ammonia-production mode for energy storage in the form of ammonia (via nitrogen reduction reaction) and an electricity-generation mode for energy conversion in the form of electricity (via ammonia oxidation reaction). This flow cell is constituted by a PtAu/C-coated nickel-foam electrode for nitrogen and oxygen reduction reactions, a Pt/C-coated nickel-foam electrode for water and ammonia oxidation reactions, and an alkaline anion exchange membrane for charge-carrier migration. Charging this flow cell with the supply of nitrogen results in a Faradaic efficiency of 2.70% and an ammonia production rate as high as 9.34 × 10 −10 mol s −1 cm −2 at 23 °C. Moreover, energizing this flow cell with ammonia results in an open-circuit voltage of 0.59 V and a peak power density of 3.31 mW cm −2 at 23 °C. A round-trip efficiency of 25.7% is realized with the constant-electrode mode. Graphical abstract: Image 1 Highlights: A flow cell integrating ammonia production and electricity generation is developed. It produces NH3 at a rate of 9.34 × 10 −10 mol s −1 cm −2 with an efficiency of 2.70%. It exhibits a voltage of 0.59 V and a peak power density of 3.31 mW cm −2 at 23 °C. A round trip efficiency of 25.7% is realized with the constant-electrode mode.